Living Language: What Is a Poem Good For? - Leggo, Carl (Journal of the Canadian Association for Curriculum Studies, 2012)
I read and write and teach poetry because I hold a long commitment to the efficacy of poetry for transforming our hearts, imaginations, intellects, conversations, and communities. I promote a curriculum of poetry as a curriculum of possibility for learning to live poetically in the world, for learning to live in the ecotone, the fecund place of tensions where conflicts are integral to vitality, education, and transformation. I often hear the question, Is it a good poem? I think we should ask, What is a poem good for? I am eager to bear witness to poetry, to invite a conversation with poets I have lingered with, to spark a little enthusiasm among others, to remind all of us that poets are pursuing their art and living with keen desire. So, in this paper I ruminate on possibilities for responding to the question, “What is a poem good for?” In my ruminations I do not attempt to be definitive; I am only eager to continue a conversation that is ongoing. I present a performative text that is both poetic and full of poetry. I invite colleagues to receive this essay like a long poem, to see with the eyes of the heart, and to hear with ears that are attuned to resonances and silences, and to linger with language and memory and hope.